Proportioning and evaluation method of anti-crack roller compacted concrete based on stone powder modification

By constructing a second-order polynomial model of the amount of stone powder and fly ash, the mix ratio design of crack-resistant RCC concrete is optimized, and the problem of performance reduction when fly ash is high is solved, the comprehensive mechanical properties of concrete are improved, and evaluation methods are provided.

CN119874296APending Publication Date: 2025-04-25SHANDONG JIANZHU UNIV
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202510114804.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing crack-resistant RCC performance decreases when the fly ash is high, and there is a lack of an optimal proportion and mechanical properties evaluation method for stone powder.

Method used

By determining the turning point of the mechanical properties of the stone powder composite cementitious material system and the single-doped fly ash gelling material system, a second-order polynomial model of the amount of stone powder and fly ash was constructed, and the mix ratio design was optimized to improve the compressive, tensile and crack resistance of concrete.

Benefits of technology

On the basis of controlling the alkali content of medium-thermal silicate cement and hydration and exothermic heat, the comprehensive mechanical properties of concrete are improved, the negative impact of fly ash dosage on performance is reduced, and a method for evaluating anti-cracking rolling concrete modified by stone powder is provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874296A_ABST
    Figure CN119874296A_ABST
Patent Text Reader

Abstract

The invention discloses a proportion and evaluation method of anti-crack roller compacted concrete based on stone powder modification. The concrete is prepared from quartz stone powder, fly ash, moderate heat Portland cement, artificial sand, quartz stone, a retarding superplasticizer and an air entraining agent. The concrete is prepared from the following components in parts by weight: 60 to 150 parts of moderate heat Portland cement, 80 to 120 parts of fly ash, 60 to 110 parts of Yingan rock powder, 110 to 180 parts of Yingan rock master batch serving as coarse aggregate, 60 to 110 parts of artificial sand fine aggregate, 0.1 to 0.17 part of naphthalene series retarding superplasticizer, 0.1 to 0.15 part of air entraining agent and 80 to 100 parts of water. According to the method, the optimal mixing amount of the stone powder can be determined, the influence of the additional mixing amounts in different proportions on the mechanical properties of the concrete can be rapidly analyzed, the actual test piece manufacturing number is greatly reduced, the material consumption is reduced, the utilization efficiency of time is increased, and the optimal mixing proportion of the concrete is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete materials, and in particular relates to a mix ratio and evaluation method of crack-resistant rolled concrete modified by stone powder. Background Art

[0002] With the development of the economy and society, the demand for electricity has increased. As the layered rolling compacted dry hard concrete material has the advantages of low cost, high construction efficiency, high density and good impermeability, roller compacted concrete is widely used in the construction of hydraulic concrete structures as a vibration compacted dry hard concrete. It will be the main hydraulic concrete structure building material in my country. However, in the preparation of roller compacted concrete, in order to reduce the impact of cracking caused by hydration heat in large-volume concrete, fly ash is usually used to partially replace cement, but too high a fly ash content will significantly reduce the performance of roller compacted concrete. In addition, the production process of traditional crack-resistant roller compacted concrete relies heavily on cement and fly ash. In the central and western regions of my country, there is a lack of fly ash resources and difficulties in resource transportation. Therefore, it is imperative to explore mineral admixtures that are easy to obtain, low in cost and effective in nearby areas to replace fly ash.

[0003] In recent years, in the study of concrete performance, it has been found that the performance of concrete can be improved in many aspects by adding various admixtures, meeting the actual needs of engineering projects. Stone powder is a by-product produced in the processing and production of stone materials. It has stable physical and chemical properties, so stone powder has been widely considered as a new type of concrete admixture. By studying the influence of different stone powder dosages on the mechanical properties of concrete, the optimal dosage is found, the concrete mix ratio is determined, and the optimal mixing scheme is found, thereby improving the various mechanical properties of concrete. Reasonable stone powder dosage can reduce production costs, reduce carbon emissions and resource consumption.

[0004] However, current research on the application of stone powder in roller-compacted concrete with equal amounts of cement replaced by fly ash still faces the problems of the optimal proportion of stone powder dosage, the mechanism of its influence on concrete performance, and the lack of a method to evaluate the mechanical properties of stone powder-modified crack-resistant roller-compacted concrete materials.

[0005] Stone powder in concrete can improve the pore structure of cement paste and the mechanical properties of rolled concrete through potential chemical activity and physical filling. Therefore, it is necessary to establish a relationship model between stone powder dosage and concrete mechanical properties based on the stone powder action mechanism, to determine the optimal stone powder dosage and concrete material mix ratio, and to propose a method for evaluating the mechanical properties of concrete. Summary of the invention

[0006] The present invention aims to solve the deficiencies of the prior art and provides the following solutions:

[0007] A mixing method for crack-resistant roller compacted concrete based on stone powder modification, wherein the concrete is prepared from dacite stone powder, fly ash, medium-heat silicate cement, artificial sand, dacite stone, slow-setting high-efficiency water-reducing agent and air-entraining agent;

[0008] The concrete mix method comprises:

[0009] Determine the cracking strength and fluidity of concrete with stone powder composite cementitious material system, determine the cracking strength, tensile strength, compressive strength and fluidity of concrete with fly ash alone as well as the curing system, and find the inflection point of the mechanical properties of concrete due to the dosage of the two concrete specimens;

[0010] Determine the aggregate particle size and amount. After the stone grading test, sand ratio and water-binder ratio selection comprehensive performance test, use the recommended mix ratio to determine the total amount of materials;

[0011] Two types of test specimens were configured: single fly ash and stone powder composite, and mechanical properties, absolute temperature rise and crack resistance tests were carried out. Multiple concrete mechanical properties were selected as evaluation indicators to determine the range of stone powder content.

[0012] Based on the actual situation and the range of the stone powder dosage, a second-order polynomial model of single mechanical properties is constructed respectively, and the extreme point of the partial derivative of the second-order polynomial model of mechanical properties is obtained to obtain the ratio combination of the stone powder and fly ash dosage;

[0013] Concrete specimens are made based on the mix ratio combination, and multiple mechanical property tests are performed on the concrete specimens. If the comprehensive strength requirements are not met, a comprehensive objective function is constructed based on the second-order polynomial model, and the extreme point of the partial derivative of the comprehensive objective function is calculated to obtain the optimal mix ratio combination of stone powder and fly ash.

[0014] Preferably, the second-order polynomial model of mechanical properties is:

[0015]

[0016] Among them, y 1 represents the compressive strength of concrete, y 2 represents the flexural strength of concrete, β 0 represents the constant term, β 1 Indicates the effect of stone powder content on mechanical properties i The linear influence coefficient, x 1 Indicates the amount of stone powder, β 2 The effect of fly ash content on mechanical properties y i The linear influence coefficient, x 2 Indicates the fly ash content, β 11 Indicates the effect of stone powder content on mechanical properties i The nonlinear influence coefficient, β 22The effect of fly ash content on mechanical properties y i The nonlinear influence coefficient, β 12 The effect of composite content on mechanical properties y i The linear influence coefficient, x 1 x 2 Indicates the composite content of stone powder and fly ash, Represents random error.

[0017] Preferably, the objective function is:

[0018] F(x 1 ,x 2 )=w 1 y 1 +w 2 y 2

[0019] Among them, w 1 represents the weight coefficient of concrete compressive performance, w 2 Represents the weight coefficient of concrete flexural performance.

[0020] The present invention also provides a crack-resistant roller compacted concrete modified by stone powder, which is prepared by the above-mentioned proportioning method, including: 60-150 parts of medium-heat silicate cement, 80-120 parts of fly ash, 60-110 parts of dacite powder, 110-180 parts of dacite masterbatch as coarse aggregate, 60-110 parts of artificial sand fine aggregate, 0.1-0.17 parts of naphthalene-based slow-setting high-efficiency water-reducing agent, 0.1-0.15 parts of air-entraining agent, and 80-100 parts of water;

[0021] The specific surface area of ​​the medium-heat silicate cement is ≥300 g / cm 3 , alkali content ≤ 0.60%;

[0022] The fly ash is Class F II fly ash, with a water requirement ratio of ≤105% and free calcium oxide of ≤1.0%.

[0023] The present invention also provides an evaluation method for crack-resistant roller compacted concrete modified by stone powder, and the evaluation method is used to evaluate the prepared crack-resistant roller compacted concrete, comprising the following steps:

[0024] The performance of the prepared concrete specimens was evaluated to obtain the impact of concrete mechanical properties in actual engineering;

[0025] The prepared concrete specimens are tested, and the obtained crack resistance, tensile strength, elastic modulus, and mortar microstructure characterization are used as evaluation indicators, normalized, and a radar chart is drawn;

[0026] The characteristic parameters of the performance indicators in the radar chart are calculated, the characteristic parameters are normalized, an evaluation vector is constructed and an evaluation function is calculated, and the concrete is evaluated by the evaluation function.

[0027] Preferably, the evaluation function is:

[0028]

[0029] Among them, m represents the number of performance indicators, n ij represents the j-th performance indicator after standardization, and θ represents the angle between adjacent ray edges in the figure.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) In the method for preparing the stone powder modified roller compacted concrete proposed in the present invention, the mix design is optimized. By determining the appropriate amount of stone powder, not only the alkali content of medium-heat silicate cement is controlled, the hydration heat is reduced, but also the influence of the reduction of the mechanical properties of concrete under the large amount of traditional fly ash is controlled. The influence of the self-shrinkage, compressive properties, tensile properties, elastic modulus and hydration heat of concrete on the mechanical properties of concrete under the amount of stone powder is relatively comprehensively considered;

[0032] (2) The present invention provides an experimental method of central composite design, which uses a second-order polynomial model to describe the relationship between the amount of stone powder and fly ash and the compressive properties of concrete. The optimal combination of stone powder and fly ash corresponding to the optimal compressive strength is determined by taking partial derivatives of the second-order polynomial, and a comprehensive objective function is constructed based on the second-order polynomial model. The extreme points of the partial derivatives of the comprehensive objective function are taken to obtain the ratio combination of stone powder and fly ash, taking into account the comprehensive mechanical properties of concrete in actual engineering; the number of actual test pieces produced is greatly reduced, the amount of materials used is reduced, and the efficiency of time utilization is increased, so as to obtain the optimal mix ratio of concrete;

[0033] (3) The concrete mechanical property evaluation method provided by the present invention explores the mechanical properties of crack-resistant rolled concrete modified with stone powder at multiple scales, including tensile strength, flexural strength, crack resistance, porosity, and pore surface area, providing a means for the research and performance improvement of concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0035] Figure 1 This is a flow chart of a proportioning method according to an embodiment of the present invention;

[0036] Figure 2 This is a flow chart of an evaluation method according to an embodiment of the present invention;

[0037] Figure 3 Schematic diagram of bimodal threshold segmentation according to an embodiment of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0040] Embodiment 1

[0041] In this embodiment, if Figure 1 As shown, a mixing method of crack-resistant roller compacted concrete based on stone powder modification, the concrete is prepared from dacite stone powder, fly ash, medium-heat silicate cement, artificial sand, dacite stone, slow-setting high-efficiency water-reducing agent and air-entraining agent;

[0042] The concrete mix methods include:

[0043] S1. Determine the crack resistance and fluidity of concrete with stone powder composite cementitious material system, determine the crack resistance, tensile strength, compressive strength and fluidity of concrete with single fly ash cementitious material system and the curing system, and find the inflection point of the mechanical properties of concrete due to the dosage of the two concrete specimens.

[0044] Before determining the crack resistance and fluidity of the composite cementitious material system concrete to be mixed, the crack-resistant roller compacted concrete material is determined first. The concrete material consists of Class F fly ash, stone powder fraction, 70-110 mesh artificial sand, 8-30 mesh small stone, 8-4 mesh medium stone, 4-2 mesh large stone, GK-4 naphthalene-based slow-setting high-efficiency water-reducing agent, and GK-9A air-entraining agent; the stones used as coarse aggregate are all dacite.

[0045] Specifically, the compressive strength test follows the "Test Procedures for Hydraulic Concrete", and a standard cubic specimen with a side length of 150mm is selected. The loading rate is controlled at 0.3-0.5MPa / s, and the compressive strength is measured at the curing age of 7d, 28d, 90d, and 180d. The tensile strength is calculated as follows:

[0046]

[0047] Among them, f ts Indicates the splitting tensile strength, MPa; p indicates the specimen failure load, N, accurate to 0.01KN; A indicates the specimen splitting area, mm 2 The elastic modulus of concrete is the secant elastic modulus of 0.5MPa to 40% of the failure stress, and the index is calculated according to the following formula:

[0048]

[0049] Where, P represents load, KN; A n Indicates the pressure bearing area of ​​the specimen, mm 2 ; ΔL represents the deformation value, mm; L 0 Indicates the gauge length for measuring deformation, mm; E c Represents the static compressive elastic modulus, GPa; further find the inflection point of the two concrete specimen dosages on the concrete mechanical properties.

[0050] S2. Determine the aggregate particle size and amount. After conducting stone grading tests, sand ratio and water-cement ratio selection comprehensive performance tests, use the recommended mix ratio to determine the total material amount.

[0051] In this embodiment, the amount of aggregate is determined. The maximum particle size of coarse aggregate in hydraulic structure roller compacted concrete can reach 40 mm. The number of particles of fine aggregate passing through a 200-mesh sieve needs to be controlled at 10% to 20%. Fillers are used to adjust the cohesiveness of concrete, and the proportion of particles passing through a 200-mesh sieve should be greater than 70%. Based on this condition, the aggregates selected are shown in Tables 1 and 2 below, where the coarse aggregate is dacite.

[0052] Table 1

[0053]

[0054] Table 2

[0055]

[0056] After comprehensive performance tests such as stone grading experiments, sand ratio, water-cement ratio selection, etc., the recommended mix ratio of three-grade RCC was first adopted to determine the total material consumption as shown in Figure 3.

[0057] Table 3

[0058]

[0059] S3. Prepare two kinds of test specimens: single fly ash and stone powder composite, and conduct mechanical property, absolute temperature rise and crack resistance tests. Select multiple concrete mechanical properties as evaluation indicators to determine the range of stone powder content.

[0060] In this embodiment, a number of concrete mechanical properties are selected as evaluation indicators, and the 28d compressive strength and tensile strength of concrete cubes are preferably used to perform performance tests on two concrete specimens to find the inflection point of their performance and determine the optimal dosage range of different additional materials for improving performance.

[0061] S4. Based on the actual situation and the range of stone powder dosage, the second-order polynomial model of single mechanical properties is constructed respectively, and the extreme points of partial derivatives of the second-order polynomial model of mechanical properties are obtained to obtain the ratio combination of stone powder and fly ash dosage.

[0062] In this embodiment, based on the actual situation and the range of stone powder content determined by the previous study, a central composite design experimental scheme is adopted to establish a mathematical model, and a quadratic polynomial model is used to describe the relationship between the stone powder content and the mechanical properties of concrete. The least squares method is used to substitute the data into the model equation and solve it to determine the estimated value of the coefficient, and at a specified age, the compression and flexural mechanical properties of the roller compacted concrete specimens with different proportions of stone powder and fly ash content are tested, and the data such as the compression performance and flexural strength are recorded. Specifically, the central composite design method is selected, and the cubic points in the design are determined according to the two variables of stone powder and fly ash content, and the stone powder content is 5% as the lower limit. Coded as -1; 25% as the upper limit, coded as 1, and the center point is coded as 0; the fly ash content is 25% as the lower limit, coded as -1; 45% as the upper limit, coded as 1, and the center point is coded as 0; Generate a test matrix based on the selected CCD, and each row of the matrix represents a set of test conditions for stone powder and fly ash content; Make concrete specimens according to the test matrix. During the production process, it is necessary to ensure that other conditions are the same except for the different stone powder and fly ash content, such as cement type, aggregate grading, water-cement ratio, mixing method, curing conditions, etc.; Conduct mechanical property tests on concrete specimens at a specified age (such as 28 days), and record data such as compressive strength and flexural strength. Further verify the model with new test data (validation set), substitute the stone powder and fly ash content in the validation set into the model, calculate the predicted mechanical property values, compare the compressive strength model with the actual measured values, and verify the goodness of fit of the model.

[0063] Specifically, the second-order polynomial model of mechanical properties is:

[0064]

[0065] Among them, y 1 represents the compressive strength of concrete, y 2 represents the flexural strength of concrete, β 0 represents the constant term, β 1 Indicates the effect of stone powder content on mechanical properties i The linear influence coefficient, x 1 Indicates the amount of stone powder, β 2 The effect of fly ash content on mechanical properties yi The linear influence coefficient, x 2 Indicates the fly ash content, β 11 Indicates the effect of stone powder content on mechanical properties i The nonlinear influence coefficient, β 22 The effect of fly ash content on mechanical properties y i The nonlinear influence coefficient, β 12 The effect of composite content on mechanical properties y i The linear influence coefficient, x 1 x 2 Indicates the composite content of stone powder and fly ash, Represents random error.

[0066] S5. Make concrete specimens based on the mix ratio combination and conduct multiple mechanical property tests on the concrete specimens. If the comprehensive strength requirements are not met, construct a comprehensive objective function based on the second-order polynomial model, and find the extreme point of the partial derivative of the comprehensive objective function to obtain the optimal mix ratio combination of stone powder and fly ash.

[0067] Construct a comprehensive objective function F(x), find the maximum value point by taking the method of partial derivatives, solve this set of equations by taking partial derivatives to obtain possible extreme points, determine the optimal combination of stone powder and fly ash content corresponding to the optimal compressive strength, and find the optimal stone powder content.

[0068] The objective function is:

[0069] F(x 1 ,x 2 )=w 1 y 1 +w 2 y 2

[0070] Among them, w 1 represents the weight coefficient of concrete compressive performance, w 2 Represents the weight coefficient of concrete flexural performance. Get the expression of the objective function, then find its partial derivative and set it to zero, solve the equations to get the best combination of stone powder and fly ash content.

[0071] A further option is the Pareto optimal method: by enumerating the combinations of stone powder and fly ash dosages within a certain range, calculating the corresponding compressive strength and flexural strength, and finding those dosage combinations that can improve either strength without deteriorating the compressive strength or the flexural strength, thus forming a Pareto optimal solution set.

[0072] Through the above-mentioned proportioning process, a specific proportion of crack-resistant roller compacted concrete based on stone powder modification can be obtained, including: 60-150 parts of medium-heat silicate cement, 80-120 parts of fly ash, 60-110 parts of dacite powder, 110-180 parts of dacite masterbatch as coarse aggregate, 60-110 parts of artificial sand fine aggregate, 0.1-0.17 parts of naphthalene-based slow-setting high-efficiency water-reducing agent, 0.1-0.15 parts of air-entraining agent, and 80-100 parts of water; the specific surface area of ​​medium-heat silicate cement is ≥300g / cm 3 , alkali content ≤0.60%; fly ash is Class F II fly ash, water requirement ratio ≤105%, free calcium oxide ≤1.0%. The medium-heat silicate cement should reach the peak time of hydration heat release in 10-12 hours. In order to prevent the excessively fast reaction of hydration heat release from causing the concrete's crack resistance to decrease and accelerate the alkali aggregate (Na2O and K2O in cement) to affect the durability and safety of the concrete structure, the present invention takes into account the production cost of dacite aggregate and micropowder, resource utilization and other factors, so as to achieve the best workability, stability and strength of concrete. The medium-heat silicate cement meets the cement hydration heat requirements in P.MH42.5 of GB / T200-2017.

[0073] In this embodiment, the mixing method of the concrete includes: mixing the medium-heat silicate cement, fly ash, dacite coarse aggregate, and artificial sand fine aggregate determined in the recommended mix ratio, and dry stirring for 2 minutes using a forced mixer. Since the main chemical components of dacite are Sio2 and Al2O3, a solution mixed with a naphthalene-based slow-setting high-efficiency water-reducing agent and an air-entraining agent is added and wet stirred for 3 minutes. Dacite within the determined stone powder dosage range is added and differentially stirred for 2 minutes.

[0074] Embodiment 2

[0075] In this embodiment, if Figure 2 As shown, a method for evaluating crack-resistant roller compacted concrete based on stone powder modification comprises the following steps:

[0076] A1. Evaluate the performance of the prepared concrete specimens to obtain the impact of concrete mechanical properties in actual engineering.

[0077] In this embodiment, the addition of stone powder in step A1 improves the grading of the concrete cementitious system, enhances the density of the mixture slurry, and has a significant impact on the performance of hydraulic concrete engineering, such as crack resistance, tensile strength, and compressive strength. Therefore, evaluation indicators are established using concrete tensile strength, concrete flexural strength, concrete crack resistance, and mortar microstructure characterization.

[0078] A2. Test the prepared concrete specimens, and use the obtained crack resistance, tensile strength, elastic modulus and mortar microstructure characterization as evaluation indicators, normalize them and draw a radar chart.

[0079] In this embodiment, the tensile strength of concrete can be tested according to the concrete splitting tensile strength test. According to the "Test Code for Hydraulic Concrete" (SL352-2020), a 150mm×150mm×150mm cubic specimen is selected, and the loading rate of the testing machine is set to 0.05MPa / s. Calculation. The static compressive elastic modulus test uses a 150mm×150mm×300mm prism specimen, with a measuring gauge length of 150mm. The loading rate of the testing machine is set to 15±3MPa / min. The secant elastic modulus of 0.5MPa~40% failure stress is taken and calculated as follows: Further flat plate restraint tests were conducted on concrete specimens. Based on the concrete flat plate cracking test method proposed by Kraai, 10,000-7 steel plate restraints and single-slot induced cracks were introduced. Electric fans were used to accelerate water loss, thereby causing drying shrinkage and reducing the number of specimens required for the test. The crack length and width were measured after 24 hours to evaluate the early cracking risk and stress development of concrete. The crack evaluation index was calculated according to the following formula:

[0080]

[0081] Among them, W i represents the maximum width of the i-th crack, mm; L i represents the maximum length of the i-th crack, mm; N represents the total number of cracks; A L Indicates the flat die area, m 2 ; c represents the total cracking area per unit area, mm 2 / m 2 . The mesostructure characterization of mortar includes two indicators: the porosity of cement mortar and the pore surface area of ​​cement mortar. The designed water-cement ratio is 0.44, and the fly ash is partially replaced by dacite powder. The 40mm×40mm×160mm hardened cement mortar prism specimens are cured for 14 days under the standard curing environment. A cylinder with a diameter of 25mm and a height of 50mm is drilled from the center of the cross section of the specimen. The pore structure characteristics are analyzed by X-CT scanning test. The 3D visualization software Avizo is used, combined with image segmentation and other technologies, to digitize and morphologically process the CT scan images, and deeply analyze the microscopic components of the material. The threshold segmentation method is used to determine the distribution of each component in the cement mortar. Further, based on the bimodal segmentation principle, the bimodal junction is selected as the characteristic threshold between different components to determine the distribution of each component in the cement mortar. Based on the bimodal segmentation principle, the “valley” at the junction of the bimodal peaks is selected as the characteristic threshold between different components and combined with multiple comparisons of CT images. By adjusting the gray value range, each component is clearly separated in different gray values, and the pore threshold segmentation effect is obtained, such as Figure 3As shown. The extracted pore part is used to obtain the three-dimensional model of the cement mortar pore part through Volume Rendering. Further, according to different thresholds, the CT image pixels of the cement mortar are divided into different categories. The image element is set as f(x, y), T is the feature threshold, and when the gray value of a pixel in the image is less than the gray value set by the boundary, the gray value is replaced by 0, otherwise it is 1. The image is converted to three-dimensionally reconstruct the specimen.

[0082] According to the extracted pores, the average, minimum, maximum, median, variance, peak and skewness of the pore parameters are obtained through the plane pore characteristics, and the pore distribution of the continuous image is analyzed. In three dimensions, the equivalent diameter is the diameter of a sphere of the same volume, which is calculated according to the following formula Among them, EqD represents the three-dimensional equivalent diameter; V represents the volume of a sphere of the same volume; the pore characteristic parameters are obtained, and the pore structure characteristics of the cement mortar are extracted and analyzed according to the section layer in the height direction to obtain the volume porosity. Further statistical analysis of the change in pore surface area is performed to obtain a table of changes in the pore surface area of ​​cement mortar with different stone powder dosages, and the pore surface area, maximum value, average value, and variance are obtained. The Z-score is used to normalize the indicators from 0 to 1, and a radar chart is drawn. Taking C25 concrete as an example, the lowest value of the compressive strength of the three groups of concrete is normalized to 0.

[0083] A3. Calculate the characteristic parameters of the performance indicators in the radar chart, normalize the characteristic parameters, construct an evaluation vector and calculate the evaluation function, and evaluate the concrete through the evaluation function.

[0084] The evaluation function is:

[0085]

[0086] Among them, m represents the number of performance indicators, n ij represents the jth performance index after standardization, and θ represents the angle between adjacent ray edges in the figure. i The larger the value is, the better the performance of the analyzed object is. i The larger it is, the better the overall performance of the analysis object is.

[0087] The embodiments described above are only descriptions of the preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for mixing crack-resistant roller compacted concrete based on stone powder modification, characterized in that: The concrete is prepared from dacite powder, fly ash, medium-heat silicate cement, artificial sand, dacite stone, slow-setting high-efficiency water-reducing agent and air-entraining agent; The concrete mix method comprises: Determine the cracking strength and fluidity of concrete with stone powder composite cementitious material system, determine the cracking strength, tensile strength, compressive strength and fluidity of concrete with fly ash alone as well as the curing system, and find the inflection point of the mechanical properties of concrete due to the dosage of the two concrete specimens; Determine the aggregate particle size and amount. After the stone grading test, sand ratio and water-binder ratio selection comprehensive performance test, use the recommended mix ratio to determine the total amount of materials; Two types of test specimens were configured: single fly ash and stone powder composite, and mechanical properties, absolute temperature rise and crack resistance tests were carried out. Multiple concrete mechanical properties were selected as evaluation indicators to determine the range of stone powder content. Based on the actual situation and the range of stone powder dosage, second-order polynomial models of single mechanical properties are constructed respectively, and the extreme points of partial derivatives of the second-order polynomial model of mechanical properties are obtained to obtain the mix ratio combination of stone powder and fly ash dosage; concrete specimens are made based on the mix ratio combination, and multiple mechanical properties tests are carried out on the concrete specimens. If the comprehensive strength requirements are not met, a comprehensive objective function is constructed based on the second-order polynomial model, and the extreme points of partial derivatives of the comprehensive objective function are obtained to obtain the optimal mix ratio combination of stone powder and fly ash dosage.

2. A method for mixing crack-resistant roller compacted concrete based on stone powder modification according to claim 1, characterized in that: The second-order polynomial model of mechanical properties is: Among them, y1 represents the compressive strength of concrete, y2 represents the flexural strength of concrete, β0 represents the constant term, and β1 represents the effect of stone powder content on mechanical properties y i The linear influence coefficient of x1 represents the amount of stone powder, and β2 represents the effect of fly ash content on mechanical properties y i The linear influence coefficient, x2 represents the fly ash content, β 11 Indicates the effect of stone powder content on mechanical properties i The nonlinear influence coefficient, β 22 The effect of fly ash content on mechanical properties y i The nonlinear influence coefficient, β 12 The effect of composite content on mechanical properties y i The linear influence coefficient, x1x2 represents the composite content of stone powder and fly ash, and ò represents the random error.

3. A mixing method for crack-resistant roller compacted concrete based on stone powder modification according to claim 2, characterized in that: The objective function is: F(x1,x2)=w1y1+w2y2 Among them, w1 represents the weight coefficient of concrete compressive performance, and w2 represents the weight coefficient of concrete flexural performance.

4. A crack-resistant roller compacted concrete modified by stone powder, prepared by the mixing method according to any one of claims 1 to 3, characterized in that: include: 60-150 parts of medium-heat Portland cement, 80-120 parts of fly ash, 60-110 parts of dacite powder, 110-180 parts of dacite masterbatch as coarse aggregate, 60-110 parts of artificial sand fine aggregate, 0.1-0.17 parts of naphthalene slow-setting high-efficiency water-reducing agent, 0.1-0.15 parts of air-entraining agent, and 80-100 parts of water; The specific surface area of ​​the medium-heat silicate cement is ≥300 g / cm 3 , alkali content ≤ 0.60%; The fly ash is Class F II fly ash, with a water requirement ratio of ≤105% and free calcium oxide of ≤1.0%.

5. An evaluation method for crack-resistant RCC modified by stone powder, the evaluation method being used to evaluate the crack-resistant RCC prepared according to claim 4, characterized in that: The following steps are involved: The performance of the prepared concrete specimens was evaluated to obtain the impact of concrete mechanical properties in actual engineering; The prepared concrete specimens are tested, and the obtained crack resistance, tensile strength, elastic modulus, and mortar microstructure characterization are used as evaluation indicators, normalized, and a radar chart is drawn; The characteristic parameters of the performance indicators in the radar chart are calculated, the characteristic parameters are normalized, an evaluation vector is constructed and an evaluation function is calculated, and the concrete is evaluated by the evaluation function.

6. The evaluation method of crack-resistant RCC based on stone powder modification according to claim 5, characterized in that: The evaluation function is: Among them, m represents the number of performance indicators, n ij represents the j-th performance indicator after standardization, and θ represents the angle between adjacent ray edges in the figure.

Citation Information

Cited By

  • Concrete mix proportion design method based on machine-made sandstone powder as cementing material

    CN120089240A

  • Performance prediction method for self-compacting geopolymer concrete based on mesoscopic model reconstruction

    CN120430088A

  • Machine-made sand concrete containing mountain flour and corresponding mix proportion design method

    CN120878004A

  • Screening evaluation method of coal-fired bottom ash aggregate and application of coal-fired bottom ash aggregate in preparation of foam concrete

    CN121354757A